The use of an intravaginal triptorelin gel to induce ovulation in the mare - Sinclair, Chelsea D. (Kansas State University, 2016)
The objective of these studies was to investigate the efficacy of an intravaginal triptorelin acetate (TA) gel as an ovulation-inducing agent in mares. In Exp 1, 24 mares were stratified by parity and age and randomly assigned to 3 treatment groups receiving either: 5 mL TA gel (500 μg TA; TA5), 10 mL TA gel (1,000 μg TA; TA10), or 5 mL vehicle gel only (CON). Following the appearance of a follicle ≥ 25 mm, blood samples were obtained every 24 h until treatment administration for measurement of luteinizing hormone (LH) concentrations. Once a follicle ≥ 35 mm in diameter was detected, treatment was administered intravaginally. Following treatment, blood samples were collected and ovaries were scanned via transrectal ultrasonography every 12 h until 48 h post-ovulation. Both TA5 and TA10 tended (P = 0.08) to experience a brief surge in LH by 12 h post-treatment. Regarding LH concentrations, there was a significant (P < 0.005) treatment by time interaction. The interval from treatment to ovulation was not different (P > 0.05) between groups, nor was there a difference (P > 0.05) in the percentage of mares ovulating within 48 h of treatment administration. We hypothesized that LH was not staying elevated long enough for ovulation to occur in a greater percentage of mares. Furthermore, more frequent sampling and scanning was needed to get a more robust characterization of the effect of TA on LH and a more accurate timeframe for when ovulation was occurring. Experiment 2 involved the same CON and TA5 treatment groups; however, the TA10 treatment was split into two 5-mL doses of TA gel, administered 24 h apart (two 500-μg doses of TA; TA5x2). Blood collection and ultrasonography occurred every 12 h upon detection of a follicle ≥ 25 mm in diameter. Once a follicle ≥ 35 mm was detected, treatment was administered and ultrasonography and blood collection occurred every 6 h until 48 h post-ovulation. Both TA5 and TA5x2 had a significant increase (P < 0.05) in LH by 6 h post-treatment, which was declining by 12 h post-treatment. The second dose administered to TA5x2 failed to elicit an increase in LH (P > 0.05). Overall, the treatment by time interaction was significant (P < 0.005) in regard to LH and the interval from treatment to ovulation was shorter (P < 0.01) in TA5 and TA5x2 compared with CON. In conclusion, TA gel increased LH concentrations and hastened the interval from treatment to ovulation in mares in Exp. 2, but not Exp. 1, without an advantage in the timing of ovulation noted between the 5 or 10-mL doses, or administration of two 5-mL doses given 24 h apart. The results of these studies suggest that further testing is needed to effectively evaluate the efficacy of TA gel as an ovulation-inducing agent in mares.
Keywords: Triptorelin; Mare; Ovulation; Intravaginal; Reproduction